2000
DOI: 10.1080/13518470050195092
|View full text |Cite
|
Sign up to set email alerts
|

Credit agency regulation and the impact of credit ratings in the international bond market

Abstract: The use of credit ratings in financial and other legal documents — both in the USA and Europe —, has led to a situation in which the major rating agencies have become (largely unwilling) participants in the legislative process. This situation has become partly formalized in the US (and is being repeated elsewhere in the European Union, Eastern Europe and Latin America) through the creation of officially 'recognized' agencies whose ratings now carry the imprimatur of the Securities and Exchange Commission. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…The sustainability of the firm demonstrates creditworthiness as part of its financial performance. Hull and White (2012) concluded that risk measures (CRA) are not value measures, ratings (S&P and Fitch) create the illusion of a free lunch, and the securitization that was observed is consistent with structures exploiting the criteria used by the rating agencies, whereas Brookfield and Ormrod (2000) claimed that official recognition of the rating of bonds/securities has no market-based role. In addition, Angilella and Mazzu (2015) reiterated that a multiple-criteria decision aid is appropriate in situations in which there is a lack or absence of analytic quantitative techniques for constructing judgemental credit assessment models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The sustainability of the firm demonstrates creditworthiness as part of its financial performance. Hull and White (2012) concluded that risk measures (CRA) are not value measures, ratings (S&P and Fitch) create the illusion of a free lunch, and the securitization that was observed is consistent with structures exploiting the criteria used by the rating agencies, whereas Brookfield and Ormrod (2000) claimed that official recognition of the rating of bonds/securities has no market-based role. In addition, Angilella and Mazzu (2015) reiterated that a multiple-criteria decision aid is appropriate in situations in which there is a lack or absence of analytic quantitative techniques for constructing judgemental credit assessment models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…146 An "outlook" contains an opinion on the likely direction of an issuer's credit quality over the medium term, while "reviews" constitute a subset of outlooks and form much stronger statements about the future direction of an issuer's credit quality, i.e., they imply that credit quality has changed to the point that the rating may need to be revised (see Hamilton and Cantor, 2004, p. 4). 147 See also Barron et al (1997); Ederington and Goh (1998);Ferri et al (1999); Kish et al (1999); Brookfield and Ormrod (2000); Gropp and Richards (2001); Hamilton and Cantor (2004); Sy (2004); Purda (2007); Ismailescu and Kazemi (2010); Bannier and Hirsch (2010). The results also hold for ratings of sovereign debt (see n. 13 and accompanying text).…”
Section: Do Ratings Communicate Valuable Information To the Market?mentioning
confidence: 87%
“… See also Barron et al (1997); Ederington and Goh (1998); Ferri et al (1999); Kish et al (1999); Brookfield and Ormrod (2000); Gropp and Richards (2001); Hamilton and Cantor (2004); Sy (2004); Purda (2007); Ismailescu and Kazemi (2010); Bannier and Hirsch (2010). The results also hold for ratings of sovereign debt (see n. 13 and accompanying text).…”
mentioning
confidence: 87%
“…Some studies such as Hand, Holthausen, and Leftwich (1992), Liu, Seyyed, and Smith (1999), Brookefield and Ormond (2000), Gabbi and Sironi (2005), for example, have argued that rated issuers provide help to mitigate the problems of asymmetric information. 3 Other authors, such as Bancel and Mitoo (2001), Houston and Jones (2002) and Yamori and Baba (2001) suggest that foreign listings, through disclosure requirements, also mitigate the information assymmetries and increase liquidity, thereby reducing borrowing costs.…”
Section: Introductionmentioning
confidence: 98%